Air carrier liability in international law, in european law and in turkish law - Güneş, Kader (My University, 2008)
‘Havayolu ile Taşıyanın Uluslarası Hukukta, Avrupa Hukukunda, ve Türk Hukukunda Sorumluluğu’ başlığı altındaki bu tezi yazmaktaki amacım hava taşıyanın sorumluluğunu Uluslarası hukuk, Türk hukuku ve Avrupa Birliği hukuku açısından karşılaştırmalı olarak incelemektir. Yedi bölümde ele alınan bu tez, hava taşımacılığı geniş bir çalışma alanını kapsadığından, esas olarak hava yük taşıyanının sorumluluğunu incelemektedir. Bu nedenle çalışmanın amacı öncelikle 1929 Varşova Konvansiyonu ile düzenlenen uluslararası havayolu ile yük taşımacılığıdır. Çalışmanın birinci bölümünde uluslararası sivil havacılıkta havayolu ile taşıyanın sorumluluğunun gelişimini, La Haye 1955 Protokolünden başlayarak 1999 Montreal Konvansiyonuna kadar olan Varşova Konvansiyonun tarihi gelişimini temel kaynaklarını, yapılan değişikleri incelenmektedir. Ayrıca bu bölümde Intercarrier Agreements (Taşıyanlar arası anlaşmalar) ve Avrupa Birliği tüzükleri incelenmektedir. İkinci bölümde Türk Sivil Havacılık Kanunu ele alınmaktadır. Üçüncü bölümde, havayolu ile yük taşıma sözleşmesi ve hava yük senedi incelenmaktedir. Dördüncü bölümde, taşıyanın borçları ve hakları ele alınmaktadır. Beşinci bölümde, taşıtanın hak ve borçları ele alınmaktadır. Altıncı bölümde, gönderilenin hak ve borçları ele alınmaktadır. Yedinci ve son bölümde, taşıyanın sorumluluğu, sorumluluk halleri ve şartları, sorumluluğun sınırlandırılması, sınırsız sorumluluk ve sorumluluk davası incelenmektedir.

With this research under the title “Air Carrier Liability in International Law, European Law and in Turkish Law’ my purpose is to analyze liability of the carrier by air by comparing and contrasting the International and Turkish law and the European Union Legislation. The thesis, which is organized in seven parts, examines mainly the liability of the air cargo carrier, since the air transport covers a large concept of study. Therefore, the object of this study is the uniform law governing international carriage by air during international transportation of cargo which is primarily regulated by the Warsaw Convention, 1929. The first part of the thesis looks the evolution of the concept of air carrier liability in international law of civil aviation, the history of the Warsaw Convention including basic sources and subsequent amendments to the Warsaw Convention beginning from the Hague Protocol 1955 to the Montreal Convention 1999. It is also dealing with the Intercarrier Agreements and European Regulations. The second part deals with Turkish Civil Aviation Act. The third part deals with the contract for the carriage of cargo by air, and the air waybill. The fourth part deals with the rights and obligations of the carrier. The fifth part deals with rights and obligations of the consignor. The sixth part deals with the rights and obligations of the consignee. The seventh and last part deals with the liability of the carrier, liability grounds and conditions, principles of limitation of liability, unlimited liability and liability suit.
Keywords: Avrupa birliği Hukuku; Hava Taşımacılığı_Hukuk; Hukuk_Avrupa Birliği; Hukuk_Türkiye